EKSPLORASI DAN IDENTIFIKASI PLASMA NUTFAH TANAMAN UWI (Dioscorea Sp) DI KABUPATEN PONOROGO - Fahrur Hidayat, Muhamad; Setyo Martono, Djoko (JURNAL AGRI-TEK, 2016)
One of the food security policy is the diversification of food consumption, for food security depends only on one type of food is very vulnerable to environmental changes lately frequent. Uwi plant (Dioscorea sp) have great opportunities in food diversification program because it is tolerant to shade and drought so suitable to be developed land dry. Uwi plant (Dioscorea sp) a local plant species that have the potential to support the food security program in Indonesia. Uwi plant (Dioscorea sp) as one kind of bulb that potentially supports the diversity of food and food security in the future. The study aims to conserve plant genetic resources Uwi as an alternative non-rice food. The study is conducting by exploration, identification can be followed Uwi plant germplasm conservation in the form of a collection of advanced research. The results showed that in Ponorogo obtained 32 asesi Uwi plant (Dioscorea sp). Taken from several districts in Ponorogo. Of the 32 species of plants Uwi (Dioscorea sp). The identified into five groups, namely: Dioscorea aculeate L by 5 asesi (gembolo, gembili, gembolo mancung, ndulak. Dioscorea alata L by 20 asesi (legi 1, legi 2, ulo, lus 1, lus 2, senggani 1, senggani 2, senggani 3, senggani 4, bangkulit 1, bangkulit 2, bangkulit 3, bangkulit 4, bangkulit 5,rondo sluku, beras, cethek, sepak, duro, war. Dioscorea bulbifera L as much as 3 asesi (sembung, lader, randu alas). Dioscorea hispida Dennst much as 1 asesi (gadung), Dioscorea pentaphylla L by 4 asesi (Katak jahe,katak 1, katak 2, katak 3).Keywords: Exploration, identification, germplasm, Uwi